Modeling Approach to Long-Term Energy Demand and Energy Policy Implications - Planning Commission (Planning Commission, 1980)
This work deals with interaction of socio-economic systems with energy demand systems. The energy sector claims for nearly 50% of the Plan allocations in the public sector. It was, therefore, necessary to. initiate-a modeling effort to look into the details of the energy sector and to identify policies for energy system management.
Government of India Planning Commission
Government of India Planning Commission